Judicial Activism by the Constitutional Court in the Frame of Check and Balances as Development Towards Juristocracy - Milzam, Qashmal; Akbar Syamsul, Asyril Rizky (IHSA Institute, 2025)
The Constitutional Court as the guardian of the constitution and the guardian of the democracy is a form of rapid progress of the modern legal state. The authority of constitutional judges is growing not only as a negative legislature, but also as a mini-positive legislature by using judicial activism so that several times it has issued ultra petitum or ultra vires decisions. This phenomenon is called jurisprudence where judicial institutions are increasingly involved in state administration and political affairs. This study uses a type of normative juridical research with a legislative approach and a case approach. The results of this study found that the Constitutional Court in creating the phenomenon of jurisprudence had a great impact on improving democracy in Indonesia and did not harm checks and balances. However, the threat still exists because constitutional judges are also ordinary human beings who can make mistakes, so internal control that refers to the code of ethics and clearer selection guidelines are the key in ensuring that the quality of constitutional judges remains fair and independent from all conflicts of interest